1997
DOI: 10.1177/107906329700900103
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Daily Stress, Coping, Problem Behavior, and Cognitive Distortions in Adolescent Sexual Offenders and Conduct-Disordered Youth

Abstract: Adolescent sexual offenders (ASOs) were compared with conduct-disordered youth (CDs) and control adolescents (CAs) on measures of stress, coping, problem behavior, and cognitive distortions. CDs scored higher than ASOs on socialized aggression, aggressive coping, avoidance coping, and coping by engaging in sexual behavior. Measures of coping and problem behaviors successfully classified approximately 80% of ASOs and CDs. ASOs and CDs were similar to each other and higher than CAs on negative automatic thoughts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Our finding that adolescents who have sexually abused other youngsters have fewer behaviour problems than clinical controls and more closely resemble normal controls is not consistent with the results of a number of previous studies conducted outside Ireland ( e.g., James & O'Neil, 1996;Hastings, Anderson, & Hemphill, 1997). This may be because more serious aggressive and abusive populations of offenders are not attending Irish treatment programmes.…”
Section: Comparison With Other Studiescontrasting
confidence: 54%
See 1 more Smart Citation
“…Our finding that adolescents who have sexually abused other youngsters have fewer behaviour problems than clinical controls and more closely resemble normal controls is not consistent with the results of a number of previous studies conducted outside Ireland ( e.g., James & O'Neil, 1996;Hastings, Anderson, & Hemphill, 1997). This may be because more serious aggressive and abusive populations of offenders are not attending Irish treatment programmes.…”
Section: Comparison With Other Studiescontrasting
confidence: 54%
“…For example, they show more behaviour problems than normal controls but not incarcerated controls; they have difficulties with making and maintaining friendships and establishing empathy with others; they have problems with impulse control, anger management and assertiveness; and they come from families characterized by a variety of problems (Graves, Openshaw, Ascoine, & Ericksen, 1996;Hastings, Anderson, & Hemphill, 1997;James & O'Neil, 1996;Monto, Zgourides, & Harris, 1998;Monto, Zgourides , Harris, & Wilson, 1994;Vizard, Monck, & Misch, 1995). Despite the burgeoning international literature in this area, few studies have been conducted on Irish adolescent sexual abusers (Carr, 1999a(Carr, ,1999bO'Reilly & Carr, 1998) and non-adjudicated abusers.…”
Section: Introductionmentioning
confidence: 99%
“…A recurring finding is the presence of a history of sexual and/or physical abuse, which has been demonstrated more frequently in sex offenders than in nonsex offenders (Fagan & Wexler, 1988;Hastings, Anderson, & Hemphill, 1997;Jonson-Reid & Way, 2001;Milloy, 1994). Mixed results have been demonstrated with respect to other characteristics (e.g.…”
mentioning
confidence: 99%
“…In contrast, some studies have found that adolescent CSA perpetrators showed significant levels of delinquent behaviour (Hastings et al, 1997;James and O'Neil, 1996).…”
Section: Comparison With Other Studiesmentioning
confidence: 86%